Linear systems and signals - B.P. Lathi (Oxford University Press, 2005)
Incorporating new problems and examples, the second edition of Linear Systems and Signals features MATLABđ material in each chapter and at the back of the book. It gives clear descriptions of linear systems and uses mathematics not only to prove axiomatic theory, but also to enhance physical and intuitive understanding